2014
DOI: 10.1039/c4tb00252k
|View full text |Cite
|
Sign up to set email alerts
|

Using metal nanoparticles as a visual sensor for the discrimination of proteins

Abstract: Protein discrimination is increasingly studied because of its roles in biological chemistry. In this study, we introduced a visual sensor using the metal nanoparticles (NPs) of Au, Ag, Cu, Ni and Co to determine the fluorescence (FL) intensity and colour changing patterns to identify ten types of proteins in a polyacrylamide gel. The synthesised NPs have little to no fluorescence, and the addition of proteins immobilised by the gel could differentially enhance the FL intensity and change the FL colour of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…In this study, the specimens with the highest tensile strength was achieved when the ultrasonic power was 120 W. This phenomenon can be explained by the change of crystal microstructures. When the ultrasonic power is relatively low, more condensed α-crystals can be formed in the specimens due to the ultrasonic vibration-promoted molecular orientation, which is consistent with the published results, [39][40][41] while the crystallinity does not change significantly, leading to the increase in mechanical properties. In addition, the crystal density in a unit area (P) can be calculated by…”
Section: Effects Of Ultrasonic Vibration On Tensile Strength and Crys...supporting
confidence: 91%
“…In this study, the specimens with the highest tensile strength was achieved when the ultrasonic power was 120 W. This phenomenon can be explained by the change of crystal microstructures. When the ultrasonic power is relatively low, more condensed α-crystals can be formed in the specimens due to the ultrasonic vibration-promoted molecular orientation, which is consistent with the published results, [39][40][41] while the crystallinity does not change significantly, leading to the increase in mechanical properties. In addition, the crystal density in a unit area (P) can be calculated by…”
Section: Effects Of Ultrasonic Vibration On Tensile Strength and Crys...supporting
confidence: 91%
“…Ouyang and coworkers have also applied their fluorescent particles to a 1D PAGE assay for protein biomarker detection. 59 Recently, Xu et al reported a near infrared sensor array of which dual ligand cofunctionalized gold nanoclusters were decorated with amino acids. This platform not only discriminated proteins at nanomolar concentrations but also serum samples collected from different stages of breast cancer patients as well as healthy people.…”
Section: From Buffer To Biological Matrices For Protein Detectionmentioning
confidence: 99%
“…As a classical linear discrimination method, LDA can transform sample data into a three-dimensional or twodimensional version displayed as a scatter plot. 25 In the plot, data of the same specimen gather around a centre to form a cluster (Fig. 2); clusters of various specimens stay far from each other.…”
Section: Linear Discriminant Analysis (Lda)mentioning
confidence: 99%